The Issue of “Zangezur Corridor” in the Current Regional Developments - Vardazaryan, Marut (Bulletin of Yerevan University D: International Relations and Political Sciences, 2023)
The article discusses unfreezing of economic and transport relations in the region after the Second Karabakh war, more specifically, the issue of “Zangezur Corridor” is observed by the Republic of Armenia as security standpoint. The article reviews United Kingdom’s Turkey’s, Russia’s, Iran’s, EU’s and US’ approaches to the issue of “Zangezur Corridor”. As a result of the involvement of the South Caucasus region in the processes of formation of a new world order, the security of the region has been eroded. As a result, the Republic, of Armenia has been facing new challenges. It is crucial to strengthen Republic of Armenia’s sovereignty and subjectivity as well as to conduct balanced foreign policy.